STANDARDIZATION OF QUALITY MANAGEMENT IN CONSTRUCTION - Pynda, Rostyslav (Journal of European Economy, 2017)
Quality standardization is especially important for companies that provide construction, installation and repair services. The subjects of the construction industry that ensure a high level of quality management systems and are capable of promptly passing the construction site with the best cost performance of construction works and services are characterized by competitive advantages. This article requires special attention to standardization of the quality of work and services in the sphere of the construction and development of regional building clusters.